Optical image conversion and encryption by diffraction, phase retrieval algorithm and incoherent superposition. (January 2017) - Chen, Linfei; Chang, Guojun; He, Bingyu; Mao, Haidan; Zhao, Daomu
Abstract: In this paper, an optical encryption system is proposed based on tricolor principle, Fresnel diffraction, and phase iterative algorithms. Different from the traditional encryption system, the encrypted image of this system is a color image and the plaintext of it is a gray image, which can achieve the combination of a color image and a gray image and the conversion of one image to another image. Phase masks can be generated by using the phase iterative algorithms in this paper. The six phase masks and the six diffracting distances are all essential keys in the process of decryption, which can greatly enhance the system security. Numerical simulations are shown to prove the possibility and safety of the method. Highlights: The proposed method can achieve the conversion of a color image to another gray image. By phase iterative algorithms, six phase masks can be cleverly designed in encryption process. By incoherent superposition, the correct information can be recovered with all the required keys. Finally, numerical simulations are shown to prove the possibility and safety of the method.